A high voltage ceramic side wall semiconductor package and a method of manufacturing the same

By setting a ceramic shoulder and a metal-free annular surface at the outlet of the through-wall metal conductor in the alumina ceramic sidewall, combined with tungsten-molybdenum-manganese metallization paste and nickel-gold termination layer, the conductor structure and insulation problems between high-voltage terminals are solved, and the withstand voltage and insulation reliability are improved.

CN123035983APending Publication Date: 2026-11-03YIXING CITY JITAI ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611546953.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-10-08
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing ceramic insulated conductor sealing technology struggles to balance the exposed state of the metal conductor at the outlet, the surface insulation path, the thickness of the ceramic sidewall, and the continuity of conductor filling in electrical connection structures with limited spacing between high-voltage terminals. This leads to increased withstand voltage and risk of partial discharge.

Method used

A ceramic shoulder is formed at the outlet of the through-wall metal conductor in the alumina ceramic sidewall. The end face of the metal conductor is retracted to form a ceramic annular surface without exposed metal. The conductor filling channel is filled with tungsten-molybdenum-manganese metallization paste and fired in a firing atmosphere composed of nitrogen and hydrogen to form a nickel-gold termination layer, ensuring conductor continuity and reliable insulation.

Benefits of technology

It improves the structural integrity and surface insulation of through-wall conductors, reduces the risk of partial discharge, and enhances the voltage withstand capability and thermal cycling stability of high-voltage electrical installations, making it suitable for high-reliability electrical connection systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123035983A_ABST
    Figure CN123035983A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ceramic insulating conductor sealing technology, and provides a high-voltage-resistant ceramic side wall semiconductor package and a preparation method thereof. The application surrounds an element accommodating cavity by an alumina ceramic base and an alumina ceramic side wall, sets a tungsten-molybdenum-manganese through-wall metal conductor in the side wall, forms a ceramic shoulder with a metal-exposed-free ceramic annular face and a controlled axial shoulder width at the outlet of the conductor to make the end face of the through-wall metal conductor retract, cooperates with a stepped through-wall hole, controlled metal filling, nitrogen-hydrogen atmosphere firing and a nickel-gold terminal layer design, makes the conduction continuity, the end face stability, the surface insulation and the terminal reliability mutually compatible, reduces the discharge risk caused by the metal end part exposure, alleviates the conflict between the slurry fluidity and the conductive reliability, and is suitable for high-voltage electrical interconnection and high-reliability ceramic packaging scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic insulated conductor sealing technology, specifically to a high-voltage ceramic sidewall semiconductor package and its preparation method. Background Technology

[0002] High-voltage electrical installations, power electronic equipment, and high-reliability electrical connection systems are increasingly used in new energy vehicles, power electronics, rail transportation, industrial control, aerospace, and high-reliability sensing systems. Insulated conductor assemblies not only need to provide conductor leads, insulation, and environmental isolation, but also need to withstand high electric fields, temperature fluctuations, and assembly stresses within a small volume. Ceramic sidewall insulated conductor assemblies, due to their high insulation strength, heat resistance, dimensional stability, and hermetically sealed adaptability, are suitable for forming a stable insulating enclosure around the component housing and achieving internal and external electrical connections through through-wall metal conductors. For electrical connection structures with limited high-voltage terminal spacing, the metal exposure near the through-wall conductor outlet, the surface insulation path, the ceramic sidewall thickness, conductor fill continuity, and the termination layer coverage all collectively affect withstand voltage capability, partial discharge risk, and long-term service reliability. Therefore, a more stable structural design is urgently needed to balance conduction reliability, structural integrity, and surface insulation. Existing partial discharge studies on ceramic substrates have shown that the local high electric field at the metallization edge is closely related to the initiation of partial discharge; adjusting the metallization structure and its relative position can change the local electric field distribution and the partial discharge initiation voltage.

[0003] Existing ceramic insulated conductor sealing technologies typically focus on improvements to the ceramic matrix composition, metallization layer, conductor paste, and conductor-insulator connection structure. For example, Chinese patent CN103732558A discloses alumina ceramics and ceramic wiring boards and packages using them, demonstrating the application foundation of alumina ceramics in electronic component packaging. However, this approach emphasizes the overall performance of the ceramic material and wiring board, without addressing the risk of surface discharge caused by metal exposure at the through-wall metal conductor exit point by establishing a local ceramic shoulder structure. Another example is Chinese patent CN105060940A, which discloses alumina multilayer ceramic metallized tungsten paste and its preparation method. It focuses on the paste flowability, thixotropy, and conductor stability during through-hole filling and functional pattern printing. However, it lacks a systematic design for the insulated conductor structure, addressing the synergistic relationship between the retracted end face of the through-wall conductor within the high-voltage ceramic sidewall, the absence of exposed metal on the ceramic annulus, and the dense conductor filling. Summary of the Invention

[0004] The purpose of this invention is to provide a high-voltage ceramic sidewall semiconductor package and its preparation method, so as to improve the problem of difficulty in simultaneously achieving structural integrity of through-wall conductors, surface insulation, termination reliability and paste processing fluidity.

[0005] To achieve the above objectives, the present invention provides a high-voltage ceramic sidewall semiconductor package and its preparation method, comprising an alumina ceramic substrate, a component receiving cavity formed by the alumina ceramic substrate and the alumina ceramic sidewall, and a tungsten-molybdenum-manganese through-wall metal conductor penetrating the alumina ceramic sidewall.

[0006] An alumina ceramic sidewall forms a ceramic shoulder at at least one exit of the through-wall metal conductor, the ceramic shoulder causing the end face of the through-wall metal conductor to retract by 0.10-0.60 mm relative to the corresponding surface of the alumina ceramic sidewall. The ceramic shoulder forms a non-metallic ceramic annular surface around the exit of the through-wall metal conductor, the radial width of which is 0.05-0.50 mm, and the shoulder width along the axial direction of the through-wall metal conductor is 0.15-0.80 mm, with the shoulder width at the same exit not less than the corresponding end face retraction.

[0007] In this specification, end face retraction refers to the distance along the axial direction of the through-wall metal conductor from the corresponding outer or inner surface of the alumina ceramic sidewall to the contactable end face of the through-wall metal conductor; a ceramic annular surface without exposed metal refers to an annular surface around the outlet of the through-wall metal conductor that is made of alumina ceramic material and is not covered by the through-wall metal conductor and the nickel-gold termination layer; the radial width of the ceramic annular surface without exposed metal refers to the minimum distance measured radially along the through-wall metal conductor between the inner and outer edges of the annular surface; for ceramic annular surfaces with uneven circumferential width, measurements are taken in at least four equal angular directions and the minimum value is taken; shoulder width refers to the distance the ceramic shoulder extends along the axial direction of the through-wall metal conductor; contactable end face refers to the end surface of the through-wall metal conductor located within the retraction area defined by the ceramic shoulder and capable of forming the nickel-gold termination layer or test electrode connection. The end-face retraction is measured along the axial direction of the through-wall metal conductor from a reference plane including the corresponding outer or inner surface to the average height of the accessible end-face area; "inner side" refers to the side facing the component receiving cavity, and "outer side" refers to the side away from the component receiving cavity. The shoulder width is specifically measured as the distance from the reference plane corresponding to the inner or outer surface to the deepest axial boundary of the ceramic shoulder forming area; when the shoulder width is greater than the end-face retraction, the central end of the through-wall metal conductor can extend into the ceramic shoulder forming area, but must not radially cover the surrounding ceramic annular area. The end-face retraction is measured on the end face of the through-wall metal conductor before the formation of the nickel-gold termination layer; when performing non-destructive measurements after the formation of the nickel-gold termination layer, the measured value of the outer surface of the termination layer is subtracted from the cross-sectionally calibrated thickness of the termination layer. Unless otherwise stated, all numerical ranges described in this specification include the endpoints.

[0008] The alumina ceramic sidewall comprises alumina, silicon dioxide, and magnesium oxide. The content of each inorganic component, expressed as oxide equivalents, is calculated based on 100 wt% of the total inorganic solid mass of the alumina ceramic sidewall: silicon dioxide 0.1-5.0 wt%, magnesium oxide 0.1-3.0 wt%, with the balance being alumina. Based on 100 wt% of the total metal mass in the through-wall metal conductor, the content of molybdenum is 0.5-15.0 wt%, manganese 0.1-10.0 wt%, and tungsten 75.0-95.0 wt%. In this paper, the contents of tungsten, molybdenum, and manganese in the through-wall metal conductor refer to the mass percentage of the corresponding metal elements in the conductor bulk. Discontinuous element diffusion zones or interfacial reaction zones are permitted at the interface between the conductor and the alumina ceramic sidewall; these interfacial regions do not alter the constraints on the metal element composition of the conductor bulk. The inorganic components of the alumina ceramic sidewall were determined by X-ray fluorescence spectroscopy with oxide equivalent normalization. The metallic composition of the through-wall metal conductor was determined by inductively coupled plasma atomic emission spectrometry or scanning electron microscopy-energy dispersive spectroscopy calibrated with standard samples within the conductor body region that avoids the conductor-ceramic interface reaction zone. The determination results of the three metal elements, tungsten, molybdenum and manganese, were normalized to 100 wt%.

[0009] A through-wall metal conductor and a ceramic shoulder constitute a ceramic shoulder embedded conductive unit. This ceramic shoulder embedded conductive unit is prepared by forming a stepped through-wall hole on an alumina ceramic sidewall blank, filling it with a tungsten-molybdenum-manganese metallization slurry, drying, firing in a nitrogen and hydrogen atmosphere, cleaning, and drying again. The stepped through-wall hole includes a conductor-filling channel extending axially along the through-wall metal conductor and a ceramic shoulder forming area located at the outlet of the conductor-filling channel. The ceramic shoulder forming area includes a ceramic annular region radially surrounding the conductor-filling channel, forming a non-metallic ceramic annular surface at the outlet. The ceramic shoulder forming area can be an enlarged-diameter cavity recessed into the alumina ceramic sidewall from a corresponding surface, with the conductor-filling channel communicating with the bottom of the enlarged-diameter cavity. When filling with the tungsten-molybdenum-manganese metallization slurry, the axial position of the central slurry end face is controlled by a temporary limiting mask matching the outlet geometry, quantitative filling, and end face leveling. When the target end face retraction is less than the shoulder width, the central slurry can extend from the conductor filling channel into the central area of ​​the expansion cavity, but must not radially cover the ceramic annular area surrounding the conductor filling channel at the bottom of the expansion cavity; when the target end face retraction is equal to the shoulder width, the central slurry end face is located at the connection boundary between the conductor filling channel and the expansion cavity.

[0010] In the high-voltage ceramic sidewall semiconductor package of the present invention, the ceramic annular region and the retracted through-wall metal conductor end face together define a ceramic shoulder at the outlet, and the ceramic annular region is not covered by the through-wall metal conductor end face or the nickel-gold termination layer.

[0011] In the ceramic shoulder embedded conductive unit, the through-wall metal conductor is continuously continuous, the retraction of the end face of the through-wall metal conductor relative to the corresponding surface of the alumina ceramic sidewall is 0.10-0.60mm, the radial width of the ceramic annular surface without exposed metal is 0.05-0.50mm, the metal filling rate in the conductor filling channel is 92.0-99.5vol, and the closed porosity in the through-wall metal conductor is 0.1-5.0vol.

[0012] In step A5, the hydrogen content in the firing atmosphere is 0.1-5.0 vol%, the firing temperature is 1350-1550℃, the firing time is 0.5-3.0 h, and the firing pressure is 0.080-0.110 MPa. In step A6, the drying temperature after cleaning is 60-100℃, and the drying time is 0.5-3.0 h. The firing atmosphere consists of nitrogen and hydrogen, with a combined volume fraction of 100.0 vol%. The firing pressure is the total absolute pressure of the firing atmosphere. Nitrogen is used as a dilution and protective gas, while hydrogen is used to control the oxygen potential in the firing environment and reduce the influence of reducible oxides on the surface of tungsten and molybdenum powders on the formation of sintering necks in the particles. The controlled amount of manganese participates in the diffusion or reaction between metal particles and in the metal-ceramic interface region during the firing process, and together with the silicon- and magnesium-containing grain boundary phases in the alumina ceramic, it affects the interface wetting, conductor densification, and interface bonding state. The firing temperature, firing time, and manganese content are jointly controlled to reduce the risk of fluctuations in conductor composition and end-face morphology caused by excessive manganese migration or volatilization. The volume fractions of nitrogen and hydrogen are calculated on a dry basis, excluding unavoidable trace impurities in industrial gases.

[0013] The tungsten-molybdenum-manganese metallization slurry is prepared through the following steps: Weighing tungsten powder, molybdenum powder, manganese powder, ethyl cellulose, and α-terpineol; premixing the tungsten powder, molybdenum powder, and manganese powder in a nitrogen atmosphere; adding ethyl cellulose and α-terpineol to the premixed metal powder and dispersing; and vacuum degassing to obtain the tungsten-molybdenum-manganese metallization slurry. In this specification, "capable of continuously filling the conductor filling channel" means that after the slurry is filled at a set filling pressure and pre-dried, when observed in a cross-section along the axial direction of the conductor filling channel, the slurry filling section is continuous through the conductor filling channel, and there are no gaps dividing the filling section into two or more unconnected parts. The non-volatile solids content of the slurry is defined as the percentage of the total mass of tungsten powder, molybdenum powder, manganese powder, and ethyl cellulose to the total mass of the tungsten-molybdenum-manganese metallization slurry, with a non-volatile solids content of 74.0-92.0 wt% and an apparent viscosity of 20-200 Pa·s. Unless otherwise stated, the apparent viscosity of the slurry in this specification refers to the viscosity after vacuum degassing at 25±1℃ and a shear rate of 100s. -1 Apparent viscosity measured under the given conditions.

[0014] Based on a total mass of 100 wt% for the tungsten-molybdenum-manganese metallized slurry, the total content of tungsten powder, molybdenum powder, manganese powder, and ethyl cellulose is 74.0-92.0 wt%, the content of ethyl cellulose is 1.0-5.0 wt%, and the balance is α-terpineol. Based on a total mass of 100 wt% for the tungsten powder, molybdenum powder, and manganese powder, the content of tungsten powder is 75.0-95.0 wt%, the content of molybdenum powder is 0.5-15.0 wt%, and the content of manganese powder is 0.1-10.0 wt%, with the sum of the mass percentages of the three metal powders being 100 wt%. When preparing slurries with different metal compositions, while maintaining the non-volatile solids content and apparent viscosity within the above-mentioned ranges, the rheological state of the slurry is corrected by adjusting the amount of α-terpineol to match the composition of the through-wall metal conductor after firing with the aforementioned tungsten-molybdenum-manganese composition range.

[0015] Alumina ceramic sidewall preforms are prepared through the following steps: Alumina powder, silica powder, and magnesium oxide powder are weighed to obtain inorganic powder; polyvinyl butyral, polyethylene glycol 400, and ethanol are added to the inorganic powder; the mixture is then shaped into a ceramic sidewall green body; the ceramic sidewall green body is dried; and the dried ceramic sidewall green body is degreased and sintered to obtain the alumina ceramic sidewall preform. The open porosity of the alumina ceramic sidewall preform is 0.1-5.0 vol%, and the inter-batch coefficient of variation for dimensional shrinkage is 0.1-3.0%. Open porosity refers to the percentage of the apparent volume of the sidewall preform containing pores connected to the outer surface of the alumina ceramic sidewall preform. The open porosity is determined using the Archimedes method after vacuum saturation, with deionized water as the test liquid, and calculated based on the dried mass, saturated mass, and suspended mass in the liquid. The inter-batch coefficient of variation for dimensional shrinkage is... according to Calculate, where, Let be the linear shrinkage rate of the i-th batch of samples in the same measurement direction and the same nominal size. ; Let be the corresponding linear dimensions of the i-th batch of samples before sintering. Let be the corresponding linear dimensions of the i-th batch of samples after sintering. Shrinkage rate of each batch The average value, sη is the linear shrinkage rate of each batch. The sample standard deviation must be calculated, and the number of batches involved in the calculation of the inter-batch coefficient of variation must be no less than 3.

[0016] In some embodiments, the alumina ceramic base is prepared using the same inorganic powder system as the alumina ceramic sidewall blank, formed into a flat ceramic part, and together with the alumina ceramic sidewall, defines the component receiving cavity during assembly. The description of the alumina ceramic sidewall as "set on" the alumina ceramic base in this specification means that the two are fixedly connected after positioning; the fixed connection can use an insulating sealing glass or inorganic ceramic adhesive material compatible with alumina ceramic, and the connection area is located at the contact interface between the alumina ceramic sidewall and the alumina ceramic base, avoiding the through-wall metal conductor outlet, the ceramic shoulder, and the exposed ceramic surface used to calculate the shortest surface distance.

[0017] In this specification, "alumina ceramic sidewall blank" refers to the sintered alumina ceramic sidewall body, after degreasing and sintering, used to form stepped through-wall holes and fill with tungsten-molybdenum-manganese metallization slurry; "ceramic sidewall green" refers to the ceramic sidewall body that has been formed but not yet sintered. When pre-forming the through-wall hole contour using compression molding, compression molding is completed during the forming stage of the ceramic sidewall green; after sintering, the through-wall hole contour can be trimmed by mechanical grinding and / or laser processing.

[0018] A nickel-gold termination layer is disposed on the accessible end face of the through-wall metal conductor, wherein the nickel-gold termination layer does not cover the ceramic annular surface without exposed metal. During the formation of the nickel-gold termination layer, the accessible end face of the through-wall metal conductor is cleaned and dried; a nickel layer is formed on the accessible end face using a nickel target as the nickel source in an argon atmosphere; a gold layer is formed on the nickel layer using a gold target as the gold source in an argon atmosphere. The nickel layer thickness is 1.0-8.0 μm, the gold layer thickness is 0.03-1.00 μm, and the continuous coverage of the termination layer on the accessible end face is 95.0-100.0%. During the formation of the nickel and gold layers, a mask matching the projection of the accessible end face is used, ensuring that the opening of the mask only exposes the accessible end face, and that the main deposition direction of the sputtered particles is aligned with the axis of the conductor filling channel; by controlling the position of the mask and the local sputtering time, the nickel and gold layers cover the accessible end face without covering the ceramic annular surface without exposed metal. Before local sputtering, the actual deposition rate at the bottom of the retracted area is calibrated on a calibration piece with the same conductor-filled channel aperture and end-face retraction. The continuous coverage of the termination layer refers to the percentage of the area of ​​the largest common coverage area on the accessible end face, where both nickel and gold layers are simultaneously present and interconnected, relative to the total area of ​​the accessible end face; isolated coverage points and coverage areas separated by exposed breaks are not included in the common continuous coverage area. "Not covering ceramic annular surfaces without exposed metal" means that, according to the microscopic imaging and elemental surface scanning detection methods described in this specification, no continuous tungsten, molybdenum, manganese, nickel, or gold coating exceeding the background threshold is detected on the ceramic annular surface.

[0019] In some embodiments, ceramic shoulders are simultaneously located at both the inner and outer outlets of the through-wall metal conductor, with both the inner and outer end faces recessed by 0.10-0.60 mm relative to the corresponding alumina ceramic sidewall surface. The high-voltage and low-voltage through-wall metal conductors are staggered in the height or circumferential direction of the alumina ceramic sidewall, with a minimum surface distance of 1.5-12.0 mm between them. The alumina ceramic sidewall has a thickness of 0.30-1.50 mm, a height of 0.60-4.00 mm, and a conductor filling channel diameter of 0.08-0.50 mm. At the same through-wall metal conductor, the thickness of the alumina ceramic sidewall is greater than the sum of the widths of the inner and outer ceramic shoulders. The shortest surface distance refers to the shortest continuous ceramic surface path length formed along the exposed surface of the alumina ceramic sidewall and the connected ceramic shoulder surface on the same side where adjacent high-voltage and low-voltage through-wall metal conductors have outlets, from the nearest edge of the contactable end face of the high-voltage end or the nickel-gold termination layer covering it to the nearest edge of the contactable end face of the low-voltage end or the nickel-gold termination layer covering it. When no nickel-gold termination layer is formed at the corresponding outlet, the nearest edge of the contactable end face of the through-wall metal conductor is used as the starting or ending point of the measurement. The outer contour of the ceramic shoulder forming area is entirely within the boundary of the corresponding surface of the alumina ceramic sidewall and does not intersect with the upper or lower edge of the alumina ceramic sidewall or the ceramic shoulder forming area of ​​the adjacent through-wall metal conductor.

[0020] This invention also discloses a method for preparing the aforementioned high-voltage ceramic sidewall semiconductor package, comprising the following steps: S1. Provides an alumina ceramic base and an alumina ceramic sidewall blank; S2. A stepped through-wall hole is formed on the alumina ceramic sidewall blank; S3. Use tungsten-molybdenum-manganese metallization paste to fill the conductor filling channel. Control the axial filling termination position of the tungsten-molybdenum-manganese metallization paste according to the target end face retraction amount, and control the tungsten-molybdenum-manganese metallization paste not to cover the ceramic annular area surrounding the conductor filling channel in the ceramic shoulder forming area. S4. Dry the filled alumina ceramic sidewall blank; S5. Firing in a firing atmosphere composed of nitrogen and hydrogen to form a through-wall metal conductor that is 0.10-0.60 mm retracted relative to the surface of the alumina ceramic sidewall; S6. After forming a nickel-gold termination layer on the accessible end face of the through-wall metal conductor, the sintered alumina ceramic sidewall is positioned and fixed on the alumina ceramic substrate, so that the alumina ceramic sidewall and the alumina ceramic substrate together define the component receiving cavity, thereby obtaining a high-voltage ceramic sidewall semiconductor package.

[0021] In step S2, the stepped through-wall hole is formed by laser processing, mechanical grinding, or a combination thereof. The conductor filling channel diameter is 0.08-0.50 mm, the shoulder width of the ceramic shoulder forming area is 0.15-0.80 mm, and the shoulder width of the ceramic shoulder forming area is not less than the corresponding target end face retraction amount. In step S3, the tungsten-molybdenum-manganese metallization slurry is filled into the conductor filling channel under a filling pressure of 0.05-0.60 MPa, and the filling is repeated 1-5 times. After each filling, it is pre-dried at 40-90℃ for 0.05-0.50 h. The filling pressure is the gauge pressure relative to the ambient pressure. Before filling, the slurry filling termination position is calibrated according to the firing axial shrinkage rate of the tungsten-molybdenum-manganese metallization slurry, and the contactable end face after firing reaches the target end face retraction amount by using a temporary limiting mask or end face leveling. After each pre-drying, the ceramic annular area is checked. If the slurry exceeds its inner edge, the slurry that exceeds the boundary is removed before subsequent overall drying.

[0022] In the preparation of tungsten-molybdenum-manganese metallization slurry, tungsten powder, molybdenum powder, and manganese powder are premixed in a nitrogen atmosphere for 0.5-3.0 h; after adding ethyl cellulose and α-terpineol, the mixture is dispersed at 20-50℃ for 1.0-4.0 h using a three-roll mill or planetary mixer; subsequently, it is vacuum degassed at a pressure of 0.001-0.020 MPa for 0.2-2.0 h. The vacuum degassed pressure is the absolute pressure inside the vacuum degassed container.

[0023] In the preparation of the alumina ceramic sidewall green body, based on a total inorganic powder mass of 100 wt%, the content of silica powder is 0.1-5.0 wt%, the content of magnesium oxide powder is 0.1-3.0 wt%, and the balance is alumina powder. Based on 100 parts by weight of inorganic powder, 3-10 parts by weight of polyvinyl butyral, 1-6 parts by weight of polyethylene glycol 400, and 30-80 parts by weight of ethanol are added. The mixture is stirred at 20-50℃ for 4-24 hours and then shaped into a ceramic sidewall green body. The ceramic sidewall green body is dried at 40-80℃ for 2-12 hours; after drying, the ceramic sidewall green body is degreased at 300-600℃ for 1-6 hours and sintered at 1500-1650℃ for 1-6 hours.

[0024] The filled alumina ceramic sidewall preform was dried at 80-120℃ for 0.2-1.5 h; the drying endpoint was defined as the mass change of the sample within 30 minutes at the same drying temperature not exceeding 0.2% of the sample mass before drying. The dried alumina ceramic sidewall preform was then fired in a firing atmosphere composed of 95.0-99.9 vol% nitrogen and 0.1-5.0 vol% hydrogen at a firing temperature of 1350-1550℃ for 0.5-3.0 h and a firing pressure of 0.080-0.110 MPa. After firing, it was cleaned with ethanol and dried at 60-100℃ for 0.5-3.0 h. The sum of the volume fractions of nitrogen and hydrogen was 100.0 vol%, and the firing pressure was the total absolute pressure of the firing atmosphere.

[0025] Metal fill rate is calculated as the percentage of the solid metal volume to the conductor filling channel volume. Closed porosity is calculated using microfocus X-ray CT 3D reconstruction results. Closed pores are defined as pores in the 3D reconstructed volume that are not connected to the outer surface of the through-wall metal conductor. The closed porosity is calculated as the percentage of the closed pore volume to the envelope volume of the through-wall metal conductor. The conductor filling channel volume does not include the expanded cavity volume of the ceramic shoulder forming region. The side length of the reconstructed voxels tested by microfocus X-ray CT is no greater than 2 μm. The grayscale segmentation threshold is calibrated using dense tungsten-molybdenum-manganese standard samples and air regions. Pores with dimensions lower than the effective spatial resolution are not included in the porosity statistics. The equivalent diameter of a closed pore is the diameter of a sphere with the same volume as the corresponding closed pore.

[0026] The apparent viscosity of the tungsten-molybdenum-manganese metallized slurry was determined after vacuum degassing. The slurry was tested before entering the conductor filling channel. The test temperature, shear rate, measured apparent viscosity value, and non-volatile solids content were recorded. The measured apparent viscosity value was used as a quality control parameter before the slurry entered the filling step. Unless otherwise specified in the rheological curve, the apparent viscosity test was performed using a rotational rheometer and a 25mm diameter parallel plate fixture with a 1.0mm test gap. After loading the sample, it was allowed to stand for 60 seconds, and then measured in 10-second increments. -1 Pre-shear for 60 seconds, then let stand for 60 seconds, followed by shearing at 25±1℃ and a shear rate of 100 seconds. -1 Under the given conditions, hold for 30 seconds, and use the average value of the last 10 seconds as the reported apparent viscosity value.

[0027] During the preparation of the nickel-gold termination layer, the accessible end face of the through-wall metal conductor is cleaned with ethanol and dried at 60-100℃ for 0.5-2.0h. When forming the nickel layer, a metallic nickel target is used as the nickel source, and the accessible end face is locally sputtered in an argon atmosphere, ensuring that the nickel layer does not cover the ceramic annular surface without exposed metal. The sputtering pressure is 1.0×10⁻⁶. -7 -1.0×10 -6At a pressure of MPa and a substrate temperature of 20-180℃, a nickel layer with a thickness of 1.0-8.0 μm is formed. For gold layer formation, a gold target is used as the gold source, and sputtering is performed locally on the nickel layer in an argon atmosphere, ensuring that the gold layer does not cover the ceramic annular surface without exposed metal. The sputtering pressure is 1.0 × 10⁻⁶ MPa. -7 -1.0×10 -6 At a pressure of MPa and a substrate temperature of 20-180℃, a gold layer with a thickness of 0.03-1.00 μm is formed. During localized sputtering, a masking membrane is used to expose only the accessible end faces, and the sputtering time is controlled according to a pre-calibrated deposition rate; the sputtering pressure is the absolute pressure within the sputtering chamber. The deposition rate is measured on a calibration specimen with the same retraction amount, conductor-filled channel aperture, and masking membrane opening size as the sample to be treated.

[0028] Inter-terminal withstand voltage and partial discharge initiation voltage are measured after the test electrodes are connected between the high-voltage and low-voltage through-wall metal conductors. The test object is the electrical insulation path formed by the alumina ceramic sidewall and its surface between the two conductors. The test uses AC RMS voltage boosting, and the applied voltage waveform, test frequency, boosting process, holding time, electrode connection method, apparent charge, background noise, and failure criteria are recorded according to IEC 60270:2025. The partial discharge measurement system is calibrated with a 5pC calibration pulse before and after the test, and the background noise of the test system is controlled below 2pC. The test electrodes are connected using elastic probes or bonding wires that match the size of the accessible end face, and it is ensured that the test electrodes and connection materials do not cross or cover the ceramic ring surface without exposed metal. The partial discharge initiation voltage test and the inter-terminal withstand voltage test use independent samples; when using the same sample, the partial discharge initiation voltage test is performed first, followed by the inter-terminal withstand voltage test. For samples that do not experience breakdown, flashover, failure, or partial discharge within the set test upper limit, the corresponding results shall be recorded according to the criteria of "not lower than the test upper limit and no corresponding failure." Unless otherwise specified, after the test samples are equilibrated in an air environment of 25±2℃ and 45±10% relative humidity for 24 hours, a 50Hz sinusoidal AC effective voltage is applied at a rate of 0.5kVrms / s. The inter-terminal withstand voltage refers to the highest applied voltage that is maintained for 60 seconds after reaching the specified test voltage or the set test upper limit without experiencing breakdown, flashover, or other insulation failure. The partial discharge initiation voltage refers to the voltage increase that is paused when the apparent charge is not less than 5pC for the first time during the voltage increase process, and the voltage is maintained for 60 seconds at the corresponding voltage. If the signal continues to appear during the voltage maintenance period, this voltage is used as the partial discharge initiation voltage; if the signal does not continue to appear, the voltage increase continues until the above criteria are met.

[0029] The change in the retraction of the through-wall metal conductor end face after thermal cycling is calculated by the difference in retraction at the same outlet before and after thermal cycling. Measurements were performed at the same designated outlet using non-destructive optical microscopy with the sample uncut before and after thermal cycling. Test record fields include the thermal cycling temperature range, heating / cooling process, holding time, number of cycles, retraction before thermal cycling, retraction after thermal cycling, and the difference between the two. The change in end face retraction is calculated by subtracting the retraction before thermal cycling from the retraction after thermal cycling; a positive value indicates an increase in retraction, and a negative value indicates a decrease. The absolute value of this change is used when evaluating thermal cycling stability.

[0030] Beneficial technical effects 1. By setting a ceramic shoulder at the outlet of the through-wall metal conductor and making the end face of the through-wall metal conductor retract relative to the surface of the alumina ceramic sidewall, a ceramic ring surface without exposed metal is formed around the outlet, which can extend or reconstruct the effective insulation path formed by the ceramic surface between the high-voltage end and the low-voltage end outlet, and alleviate the local electric field concentration between the high-voltage terminals.

[0031] 2. By combining the conductor filling channel with the ceramic shoulder forming area through stepped through-wall holes, the tungsten-molybdenum-manganese metallization paste mainly fills the conductor filling channel, while the ceramic shoulder forming area retains the ceramic annular surface, which can control the exposed state of the end face while maintaining the continuity of the conductor.

[0032] 3. By controlling the solid content, apparent viscosity, premixing, dispersion and vacuum degassing state of the tungsten-molybdenum-manganese metallization slurry, a continuous slurry filling section can be formed in the fine conductor filling channel, and a high metal filling rate and controlled closed porosity can be obtained after firing.

[0033] 4. By constructing alumina ceramic sidewalls with alumina, silicon dioxide and magnesium oxide, and firing through-wall metal conductors in a firing atmosphere composed of nitrogen and hydrogen, the sintering microstructure of alumina ceramic sidewalls, conductor densification and conductor-ceramic interface bonding state can be synergistically controlled, thereby helping to balance sidewall dimensional stability, conductor sintering continuity and thermal cycling stability.

[0034] 5. By forming a nickel-gold termination layer on the accessible end face of the through-wall metal conductor, and making the nickel and gold layers form a common continuous coverage area without covering the ceramic annular surface without exposed metal, combined with the staggered setting of the through-wall metal conductors at the high-voltage and low-voltage ends and the control of the shortest surface distance, it is helpful to form a highly reliable ceramic insulated conductor assembly suitable for high-voltage electrical interconnection scenarios. Attached Figure Description

[0035] Figure 1 The graph shows the effect of filling pressure on metal filling rate and partial discharge initiation voltage in Example 1.

[0036] Figure 2The images show the quantitative diagrams of end face retraction in cross-sectional images of Examples 1, 9, and 10.

[0037] Figure 3 The apparent charge-applied voltage curves are for Examples 1, 9, and 10.

[0038] Figure 4 The diagram shows the equivalent diameter distribution curves of closed pores in Examples 1, 5, and 11.

[0039] Figure 5 Rheological curves of the tungsten-molybdenum-manganese metallization slurry of Example 1 and Comparative Example 5, and the tungsten-molybdenum metallization slurry of Comparative Example 11.

[0040] Figure 6 The images show a comparison of the SEM morphology and SEM-EDS mapping of the final product of Example 1 and the final product of Comparative Example 9; where, Figure 6 Figure a in the image is a low-magnification SEM image of the final product of Example 1; Figure 6 Figure b in the figure is a low-magnification SEM image of the final product of Comparative Example 9; Figure 6 Figure c in the image is a medium-magnification SEM image of the ceramic shoulder and end face retraction structure at the outer outlet of the final product of Example 1. Figure 6 The d-image in the image is a medium-magnification SEM image of the straight through-wall hole and the flush metal end face at the outer outlet of the final product of Comparative Example 9. Figure 6 Figure e in the image is a high-magnification SEM image of a local interface between the alumina ceramic, the final product of Example 1, and the tungsten-molybdenum-manganese through-wall metal conductor. Figure 6 Figure f in the figure is a high-magnification SEM image of the local contact area between the metallic phase and the outer surface of the ceramic near the flush end face of the final product of Comparative Example 9. Figure 6 The g-plot in the figure is the SEM-EDS mapping plot of the final product of Example 1; Figure 6 The h-plot in the figure is the SEM-EDS mapping plot of the final product of Comparative Example 9. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be described below with reference to the accompanying drawings. Unless otherwise stated, the numerical values ​​in the embodiments and comparative examples are obtained according to the aforementioned test methods and rounded to the indicated decimal places; the "±" in "mean ± standard deviation" represents the sample standard deviation of repeated measurements and does not represent an expansion or reduction of the numerical range of the corresponding claims.

[0042] Example 1 In this embodiment, 20 high-voltage ceramic sidewall semiconductor packages are fabricated. Each component includes an alumina ceramic substrate, an alumina ceramic sidewall, a tungsten-molybdenum-manganese through-wall metal conductor, and a nickel-gold termination layer. The alumina ceramic sidewall and the alumina ceramic substrate together form a component housing cavity with a rectangular frame structure. The sidewall thickness is 0.30 mm, and the sidewall height is 0.60 mm. The high-voltage and low-voltage through-wall metal conductors are staggered, with a minimum surface distance of 1.5 mm between them.

[0043] S1: Preparation of alumina ceramic sidewall green body. Commercially available alumina powder, silica powder, and magnesium oxide powder were weighed as inorganic powders, each with a purity of not less than 99.5% and an average particle size of 0.5 μm. Based on a total inorganic powder mass of 100 wt%, silica powder accounted for 0.1 wt%, magnesium oxide powder for 0.1 wt%, and alumina powder for 99.8 wt%. Based on 100 parts by weight of inorganic powder, 3 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, and 30 parts by weight of ethanol were added. The mixture was ball-milled at 20°C for 4 hours to form a ceramic sidewall green body. The ceramic sidewall green body was dried at 40°C for 2 hours, degreased at 300°C for 1 hour, and sintered at 1500°C for 1 hour to obtain the alumina ceramic sidewall green body. The open porosity of the alumina ceramic sidewall green body was 0.1 vol%, and the batch-to-batch coefficient of variation for dimensional shrinkage was 0.1%. The alumina ceramic base is prepared into a flat ceramic part using the same inorganic powder system.

[0044] S2: Stepped through-wall hole formation: Stepped through-wall holes are formed on the alumina ceramic sidewall blank using laser processing. The stepped through-wall holes include a conductor-filling channel and a ceramic shoulder forming area located at the outer exit. The conductor-filling channel has a diameter of 0.08 mm, and the shoulder forming area has a shoulder width of 0.15 mm. Using the corresponding outer surface of the alumina ceramic sidewall as a reference, the target end face retraction after firing is set to 0.10 mm, and the target minimum radial width of the ceramic annulus without exposed metal is 0.05 mm.

[0045] S3: Preparation of tungsten-molybdenum-manganese metallization slurry. Commercially available tungsten powder, molybdenum powder, manganese powder, ethyl cellulose, and α-terpineol were weighed. The purity of all metal powders was not less than 99.5%, and the average particle size was 1.0 μm. Based on a total mass of 100 wt% for the tungsten-molybdenum-manganese metallization slurry, the composition was 70.0 wt% tungsten powder, 2.0 wt% molybdenum powder, 1.7 wt% manganese powder, 1.0 wt% ethyl cellulose, and 25.3 wt% α-terpineol. The tungsten, molybdenum, and manganese powders were premixed in a nitrogen atmosphere for 0.5 h. After adding ethyl cellulose and α-terpineol, the mixture was dispersed using a three-roll mill at 20°C for 1.0 h, and then vacuum degassed at 0.001 MPa for 0.2 h to obtain the tungsten-molybdenum-manganese metallization slurry. The slurry contains 74.7 wt% non-volatile solids, consisting of tungsten powder, molybdenum powder, manganese powder, and ethyl cellulose, and has an apparent viscosity of 20 Pa·s.

[0046] S4: Conductor filling and pre-drying. The degassed tungsten-molybdenum-manganese metallization slurry is filled into the conductor filling channel under a filling pressure of 0.05 MPa, once per filling cycle. After each filling, it is pre-dried at 40°C for 0.05 h to form a continuous slurry filling section extending along the channel. A temporary limiting mask matching the outer outlet is used during filling, and the central slurry end face is leveled according to the filling termination position calibrated by firing shrinkage, ensuring the ceramic annular area remains free of slurry coverage. The filled alumina ceramic sidewall preform is dried at 80°C for 0.2 h, with the drying endpoint determined by a sample mass change of no more than 0.2% within 30 min.

[0047] S5: Firing and Cleaning / Drying. The dried alumina ceramic sidewall preform was placed in a firing atmosphere composed of 99.9 vol% nitrogen and 0.1 vol% hydrogen, and fired at 1350℃ for 0.5 h at a firing pressure of 0.080 MPa. After firing, the contact surfaces of the through-wall metal conductors were cleaned with ethanol and dried at 60℃ for 0.5 h to obtain the ceramic shoulder embedded conductive unit. The metal filling rate in the conductor filling channel was 92.0 vol%, and the closed porosity in the through-wall metal conductor was 5.0 vol%.

[0048] S6: For termination layer and component assembly, the accessible end face of the through-wall metal conductor is cleaned with ethanol and dried at 60°C for 0.5 hours. A nickel layer is formed by local sputtering of the accessible end face using a nickel target as the nickel source in an argon atmosphere at a sputtering pressure of 1.0 × 10⁻⁶. -7 The sputtering pressure was MPa, the substrate temperature was 20℃, and the nickel layer thickness was 1.0 μm. A gold layer was formed by localized sputtering on the nickel layer using a gold target as the gold source in an argon atmosphere. The sputtering pressure was 1.0 × 10⁻⁶ MPa. -7The pressure is MPa, the substrate temperature is 20℃, and the gold layer thickness is 0.03μm. The continuous coverage of the termination layer on the contactable end face is 95.0%. Neither the nickel nor the gold layer covers the ceramic annulus without exposed metal. The sintered alumina ceramic sidewalls are positioned and fixed on the alumina ceramic substrate, so that the alumina ceramic sidewalls and the alumina ceramic substrate together define the device receiving cavity, resulting in a high-voltage ceramic sidewall semiconductor package.

[0049] Quality inspection methods and results: Optical microscopy and cross-sectional microscopic imaging were used to statistically measure the retraction of the through-wall metal conductor end face, the radial width of the ceramic annulus without exposed metal, and the shoulder width of the ceramic shoulder. Four outlet positions were counted for each sample, and three samples were randomly selected from 20 samples for measurement. The measured retraction was 0.10±0.01 mm, the radial width of the ceramic annulus without exposed metal was 0.05±0.01 mm, and the shoulder width of the ceramic shoulder was 0.15±0.01 mm. The continuous coverage of the termination layer on the accessible end face was calculated using microscopic image area statistics, and the result was 95.0±0.5%. Using the high-voltage and low-voltage through-wall metal conductors as electrode connection objects, the measured inter-terminal withstand voltage was 5.0±0.1 kVrms, and the partial discharge initiation voltage was 3.0±0.1 kVrms. The shrinkage at the same outer outlet was measured before and after thermal cycling. The average change in shrinkage at the end face of the through-wall metal conductor after thermal cycling was 0.030±0.005mm.

[0050] This embodiment employs structural dimensions close to the lower limit within each parameter range and relatively mild fabrication conditions, making it suitable for small high-voltage insulated conductor connections, low-energy sintering fabrication, and electrical interconnection scenarios where compact component housing volume is required.

[0051] Example 2 Ten high-voltage ceramic sidewall semiconductor packages were fabricated according to this embodiment. The package comprises an alumina ceramic substrate, alumina ceramic sidewalls, a tungsten-molybdenum-manganese through-wall metal conductor, and a nickel-gold termination layer. The alumina ceramic sidewalls are 1.50 mm thick and 4.00 mm high. Ceramic shoulders are provided at both the inner and outer exits of the through-wall metal conductor. The inner shoulder is 0.80 mm wide, and the outer shoulder is 0.65 mm wide, totaling 1.45 mm, which is less than the thickness of the alumina ceramic sidewall. The high-voltage and low-voltage through-wall metal conductors are staggered circumferentially, with a minimum surface distance of 12.0 mm.

[0052] Commercially available alumina powder, silica powder, and magnesium oxide powder were weighed as inorganic powders, each with a purity of not less than 99.5% and an average particle size of 0.7 μm. Based on a total inorganic powder mass of 100 wt%, the composition was 5.0 wt% silica powder, 3.0 wt% magnesium oxide powder, and 92.0 wt% alumina powder. Based on 100 parts by weight of inorganic powder, 10 parts by weight of polyvinyl butyral, 6 parts by weight of polyethylene glycol 400, and 80 parts by weight of ethanol were added and mixed at 50°C for 24 h to form a ceramic sidewall green body. The ceramic sidewall green body was dried at 80°C for 12 h, degreased at 600°C for 6 h, and sintered at 1650°C for 6 h to obtain an alumina ceramic sidewall green body. The open porosity of the alumina ceramic sidewall green body was 5.0 vol%, and the batch-to-batch coefficient of variation for dimensional shrinkage was 3.0%. The alumina ceramic base is prepared into a flat ceramic part using the same inorganic powder system.

[0053] A stepped through-wall hole was formed on the alumina ceramic sidewall blank using a combination of mechanical grinding and laser processing. The conductor filling channel diameter was 0.50 mm, and ceramic shoulder forming areas were created on both the inner and outer outlets. After firing, the shrinkage of the inner and outer end faces relative to the corresponding alumina ceramic sidewall surfaces was 0.60 mm, and the radial width of the ceramic annular surface without exposed metal was 0.50 mm. The tungsten-molybdenum-manganese metallization slurry had a non-volatile solids content of 92.0 wt% containing ethyl cellulose and an apparent viscosity of 200 Pa·s as pre-filling quality control parameters. The slurry was filled into the conductor filling channel at a filling pressure of 0.60 MPa, with five filling cycles, followed by pre-drying at 90°C for 0.50 h after each filling. During the filling process, temporary limiting masks on the inner and outer sides were used to control the axial position of the central slurry end face, ensuring that the ceramic annular areas on both sides were free of slurry coverage. The filled alumina ceramic sidewall blank was dried at 120°C for 1.5 h.

[0054] Based on a total mass of 100 wt% for the tungsten-molybdenum-manganese metallized slurry, the composition includes 78.0 wt% tungsten powder, 8.0 wt% molybdenum powder, 4.0 wt% manganese powder, 2.0 wt% ethyl cellulose, and 8.0 wt% α-terpineol. The tungsten, molybdenum, and manganese powders were premixed in a nitrogen atmosphere for 2.5 h. After adding ethyl cellulose and α-terpineol, the mixture was dispersed at 45°C for 3.5 h using a planetary stirrer, followed by vacuum degassing at 0.015 MPa for 1.6 h.

[0055] The firing process employed a firing atmosphere consisting of 95.0 vol% nitrogen and 5.0 vol% hydrogen, at a firing temperature of 1550℃, a firing time of 3.0 h, and a firing pressure of 0.110 MPa. After firing, the sample was cleaned with ethanol and dried at 100℃ for 3.0 h. The metal filling rate was 99.5 vol%, and the closed porosity was 0.1 vol%.

[0056] The accessible surfaces of the through-wall metal conductors were cleaned with ethanol and dried at 100°C for 2.0 h. A nickel layer was formed using a nickel target as the nickel source in an argon atmosphere at a sputtering pressure of 1.0 × 10⁻⁶. -6 The sputtering pressure was MPa, the substrate temperature was 180℃, and the nickel layer thickness was 8.0 μm. A gold layer was formed on the nickel layer using a gold target as the gold source in an argon atmosphere, with a sputtering pressure of 1.0 × 10⁻⁶ MPa. -6 The substrate temperature was 180℃, and the gold layer thickness was 1.00 μm. The continuous coverage of the nickel-gold termination layer on the accessible end face was measured to be 99.9 ± 0.1%. Neither the nickel nor the gold layer covered the ceramic annulus without exposed metal. The sintered alumina ceramic sidewalls were positioned and fixed onto the alumina ceramic substrate, so that the alumina ceramic sidewalls and the alumina ceramic substrate together defined the device housing cavity, resulting in a high-voltage ceramic sidewall semiconductor package.

[0057] Cross-sectional microscopic images were used to statistically analyze the conductor-filled channel diameter, ceramic shoulder width, retraction amount, and radial width of the ceramic toroidal surface without exposed metal. The measured conductor-filled channel diameter was 0.50±0.01 mm, the inner retraction amount was 0.60±0.01 mm, the outer retraction amount was 0.60±0.01 mm, the radial width of the ceramic toroidal surface without exposed metal was 0.50±0.01 mm, the inner ceramic shoulder width was 0.80±0.01 mm, and the outer ceramic shoulder width was 0.65±0.01 mm. The metal fill rate was 99.5±0.2 vol%. The inter-terminal withstand voltage was not less than 20.0 kVrms, with a test upper limit of 20.0 kVrms and no sample failure; the partial discharge initiation voltage was not less than 15.0 kVrms, with a test upper limit of 15.0 kVrms and no partial discharge occurred. The average change in shrinkage at the same outlet end face after thermal cycling was 0.000 ± 0.003 mm. The coefficient of variation for shrinkage between batches was 5.0%, and the coefficient of variation for the width of the ceramic shoulder was also 5.0%.

[0058] This embodiment employs a larger sidewall height, a longer surface distance, a larger conductor channel aperture, a larger retraction amount, and a radial width of the ceramic annulus without exposed metal, making it suitable for high-voltage insulated conductor connection scenarios where high-end inter-subsidiary withstand voltage requirements are needed.

[0059] Example 3 In this embodiment, 15 high-voltage ceramic sidewall semiconductor packages were fabricated. The products utilize an alumina ceramic substrate, alumina ceramic sidewalls, tungsten-molybdenum-manganese through-wall metal conductors, and nickel-gold termination layers. The components are designed primarily for process adaptability. The alumina ceramic sidewalls are 0.90 mm thick and 2.20 mm high. The shortest surface distance between the high-voltage and low-voltage through-wall metal conductors is 6.0 mm, and the conductor-filled channel aperture is 0.25 mm.

[0060] The key structural parameters of this embodiment are as follows: the alumina ceramic sidewall contains 2.5 wt% silica, 1.5 wt% magnesium oxide, and 96.0 wt% alumina; the inner end face retraction is 0.12 mm, the outer end face retraction is 0.12 mm, the radial width of the ceramic annulus without exposed metal is 0.25 mm, and the shoulder width of both the inner and outer ceramic shoulders is 0.30 mm.

[0061] Alumina ceramic sidewall preforms were prepared using commercially available alumina powder, silica powder, and magnesium oxide powder, with a powder purity of not less than 99.5%. Based on 100 parts by weight of inorganic powder, 6 parts by weight of polyvinyl butyral, 3 parts by weight of polyethylene glycol 400, and 50 parts by weight of ethanol were added and mixed at 30°C for 12 hours to form a ceramic sidewall green body. Pre-formed through-wall hole contours were pre-molded during the forming of the ceramic sidewall green body. The ceramic sidewall green body was dried at 60°C for 6 hours, degreased at 450°C for 3 hours, and sintered at 1580°C for 3 hours to obtain the alumina ceramic sidewall preform. The open porosity of the alumina ceramic sidewall preform was 2.5 vol%, and the batch-to-batch coefficient of variation for dimensional shrinkage was 1.5%. The alumina ceramic base was prepared as a flat ceramic piece using the same inorganic powder system.

[0062] After sintering, the stepped through-wall holes were mechanically ground and finished. The tungsten-molybdenum-manganese metallization slurry was prepared with 80.0 wt% tungsten powder, 5.0 wt% molybdenum powder, 3.0 wt% manganese powder, 3.0 wt% ethyl cellulose, and 9.0 wt% α-terpineol. The tungsten, molybdenum, and manganese powders were premixed in a nitrogen atmosphere for 1.5 h. After adding ethyl cellulose and α-terpineol, the mixture was dispersed in a three-roll mill at 35°C for 2.5 h, followed by vacuum degassing at 0.008 MPa for 1.0 h. The non-volatile solids content of the slurry, consisting of tungsten, molybdenum, manganese, and ethyl cellulose, was 91.0 wt%, and the apparent viscosity was 80 Pa·s.

[0063] Tungsten-molybdenum-manganese metallization slurry was filled into the conductor channel under a filling pressure of 0.20 MPa, with two filling cycles. After each filling, the material was pre-dried at 60°C for 0.20 h. During the filling process, the axial termination position of the inner and outer slurry end faces was controlled according to the target end face retraction of 0.12 mm, ensuring that the ceramic annular areas on both sides were free of slurry coverage. The filled alumina ceramic sidewall preform was dried at 100°C for 0.8 h. The firing atmosphere consisted of 99.9 vol% nitrogen and 0.1 vol% hydrogen, with a firing temperature of 1350°C, a firing time of 0.5 h, and a firing pressure of 0.080 MPa. After firing, the preform was cleaned with ethanol and dried at 60°C for 0.5 h. The resulting through-wall metal conductor was continuous, with a metal filling rate of 95.0 vol% and a closed porosity of 5.0 vol%.

[0064] When forming a nickel-gold termination layer on the contactable end face of a through-wall metal conductor, the material is first cleaned with ethanol and dried at 60°C for 0.5 h, then sputtered in an argon atmosphere to form a 1.0 μm nickel layer and a 0.03 μm gold layer, both at a sputtering pressure of 1.0 × 10⁻⁶. -7 MPa, substrate temperature 20℃. The nickel-gold termination layer has a continuous coverage of 95.0% on the contactable end face. Neither the nickel nor gold layer covers the ceramic annulus without exposed metal. The sintered alumina ceramic sidewall is positioned and fixed onto the alumina ceramic substrate, so that the alumina ceramic sidewall and the alumina ceramic substrate together define the component housing cavity, resulting in a high-voltage ceramic sidewall semiconductor package.

[0065] Statistical analysis using cross-sectional micrographs revealed that the conductor-filled channel diameter was 0.25±0.01 mm, the retraction of both the inner and outer end faces was 0.12±0.01 mm, the radial width of the ceramic annulus without exposed metal was 0.25±0.01 mm, and the shoulder width of the ceramic portion was 0.30±0.01 mm. The metal filling rate was 95.0±0.4 vol%, and the closed porosity was 5.0±0.2 vol%. The inter-terminal withstand voltage was 10.0±0.2 kVrms, and the partial discharge initiation voltage was 8.0±0.2 kVrms. The average change in retraction of the through-wall metal conductor end face after thermal cycling was 0.020±0.004 mm. The batch-to-batch coefficient of variation for both the retraction and the ceramic shoulder width was 0.1%.

[0066] This embodiment is applicable to scenarios involving low thermal budget processes, composite-formed through-wall holes, and ceramic sidewall insulated conductor connections with high requirements for process window adaptability.

[0067] Example 4 This embodiment fabricates 12 high-voltage ceramic sidewall semiconductor packages. The products include an alumina ceramic substrate, alumina ceramic sidewalls, a tungsten-molybdenum-manganese through-wall metal conductor, and a nickel-gold termination layer. The alumina ceramic sidewalls are 1.50 mm thick and 0.60 mm high. Ceramic shoulders are provided at both the inner and outer exits of the through-wall metal conductor. The inner shoulder is 0.65 mm wide, and the outer shoulder is 0.80 mm wide, totaling 1.45 mm. The conductor filling channel has a diameter of 0.08 mm. The high-voltage and low-voltage through-wall metal conductors are staggered, with a minimum surface distance of 12.0 mm.

[0068] Commercially available alumina powder, silica powder, and magnesium oxide powder were weighed, with a purity of not less than 99.5%. Based on a total inorganic powder mass of 100 wt%, the silica powder was 0.1 wt%, the magnesium oxide powder was 3.0 wt%, and the alumina powder was 96.9 wt%. Based on 100 parts by weight of inorganic powder, 10 parts by weight of polyvinyl butyral, 6 parts by weight of polyethylene glycol 400, and 80 parts by weight of ethanol were added. The mixture was stirred at 50°C for 24 hours and then formed into a ceramic sidewall green body. The pre-formed through-hole contours were pre-molded during the forming of the ceramic sidewall green body. The ceramic sidewall green body was dried at 80°C for 12 hours, degreased at 600°C for 6 hours, and sintered at 1650°C for 6 hours to obtain an alumina ceramic sidewall green body. The open porosity of the alumina ceramic sidewall green body was 0.1 vol%, and the batch-to-batch coefficient of variation for dimensional shrinkage was 3.0%. The alumina ceramic base is prepared into a flat ceramic part using the same inorganic powder system.

[0069] Based on a total mass of 100 wt% for the tungsten-molybdenum-manganese metallized slurry, the following components were weighed: 86.0 wt% tungsten powder, 4.0 wt% molybdenum powder, 1.0 wt% manganese powder, 1.0 wt% ethyl cellulose, and 8.0 wt% α-terpineol. The tungsten, molybdenum, and manganese powders were all commercially available powders with a purity of not less than 99.5% and an average particle size of 0.8 μm. The tungsten, molybdenum, and manganese powders were premixed in a nitrogen atmosphere for 3.0 h. After adding ethyl cellulose and α-terpineol, the mixture was dispersed at 50 °C for 4.0 h using a planetary stirrer, followed by vacuum degassing at 0.020 MPa for 2.0 h to obtain the tungsten-molybdenum-manganese metallized slurry. The non-volatile solids content of the tungsten, molybdenum, manganese, and ethyl cellulose in the slurry was 92.0 wt%, and the apparent viscosity was 200 Pa·s.

[0070] After sintering, the stepped through-wall holes were finished using laser processing. The degassed tungsten-molybdenum-manganese metallization slurry was filled into the conductor channels under a filling pressure of 0.60 MPa, with five filling cycles. After each filling, the slurry was pre-dried at 90°C for 0.50 h. During the filling process, temporary inner and outer limiting masks were used to control the slurry end faces, ensuring that the shrinkage of both inner and outer end faces after firing reached 0.60 mm, and ensuring that the ceramic annular areas on both sides were not covered by the slurry. The filled alumina ceramic sidewall blank was dried at 120°C for 1.5 h. The firing atmosphere consisted of 95.0 vol% nitrogen and 5.0 vol% hydrogen, the firing temperature was 1550°C, the firing time was 3.0 h, and the firing pressure was 0.110 MPa. After firing, the blank was cleaned with ethanol and dried at 100°C for 3.0 h. The metal filling rate was 99.5 vol%, and the closed porosity was 0.1 vol%.

[0071] The accessible end faces of the through-wall metal conductors were cleaned with ethanol and dried at 100°C for 2.0 h. A nickel layer was formed using a nickel target as the nickel source in an argon atmosphere, with a sputtering pressure of 1.0 × 10⁻⁶. -6 The sputtering pressure was MPa, the substrate temperature was 180℃, and the nickel layer thickness was 8.0 μm. A gold layer was formed on the nickel layer using a gold target as the gold source in an argon atmosphere, with a sputtering pressure of 1.0 × 10 MPa. -6 The substrate temperature was 180℃, and the gold layer thickness was 1.00 μm. The continuous coverage of the nickel-gold termination layer on the accessible end face was measured to be 99.9 ± 0.1%. Neither the nickel nor the gold layer covered the ceramic annulus without exposed metal. The sintered alumina ceramic sidewalls were positioned and fixed onto the alumina ceramic substrate, so that the alumina ceramic sidewalls and the alumina ceramic substrate together defined the device housing cavity, resulting in a high-voltage ceramic sidewall semiconductor package.

[0072] Three samples were tested using optical microscopy, cross-sectional microscopic imaging statistics, and electrical performance testing. The retraction of the inner through-wall metal conductor end face was 0.60±0.01 mm, the retraction of the outer through-wall metal conductor end face was 0.60±0.01 mm, the radial width of the ceramic annulus without exposed metal was 0.05±0.01 mm, the shoulder width of the inner ceramic shoulder was 0.65±0.01 mm, and the shoulder width of the outer ceramic shoulder was 0.80±0.01 mm. The inter-terminal withstand voltage was not less than 20.0 kVrms, with a test upper limit of 20.0 kVrms and no sample failure; the partial discharge initiation voltage was not less than 15.0 kVrms, with a test upper limit of 15.0 kVrms and no partial discharge occurred. The average change in the retraction of the through-wall metal conductor end face after thermal cycling was 0.030±0.003 mm. The coefficient of variation for shrinkage was 5.0% between batches, and the coefficient of variation for the width of the ceramic shoulder was 5.0% between batches.

[0073] This embodiment uses a combination of a relatively wide outer ceramic shoulder and an inner ceramic shoulder that meets the end face retraction support requirements. It is combined with high firing strength, high filling pressure, thicker termination layer and longer surface distance, making it suitable for high-voltage power electrical connection structures with sufficient external terminal side insulation, limited internal electrical connection space and high thermal cycling reliability requirements.

[0074] Comparative Example 1: It is basically the same as Example 1, except that in step S1, the content of silica powder is adjusted to 0.0 wt%, magnesium oxide powder to 0.1 wt%, and aluminum oxide powder to 99.9 wt%, while other conditions remain unchanged.

[0075] Comparative Example 2: It is basically the same as Example 1, except that in step S1, the content of magnesium oxide powder is adjusted to 0.0 wt%, silicon dioxide powder to 0.1 wt%, and aluminum oxide powder to 99.9 wt%, while other conditions remain unchanged.

[0076] Comparative Example 3: It is basically the same as Example 1, except that in step S2 the diameter of the conductor filling channel is adjusted to 0.06 mm, the width of the shoulder of the ceramic shoulder forming area is still 0.15 mm, and other conditions remain unchanged.

[0077] Comparative Example 4: It is basically the same as Example 1, except that in step S2, the radial width of the ceramic annulus without exposed metal is adjusted to 0.02 mm, the retraction of the end face of the through-wall metal conductor is still 0.10 mm, the shoulder width of the ceramic shoulder forming area is still 0.15 mm, and other conditions remain unchanged.

[0078] Comparative Example 5: It is basically the same as Example 1, except that the filling pressure of the tungsten-molybdenum-manganese metallization slurry in step S4 is adjusted to 0.02 MPa, the number of fillings is still 1, and it is still pre-dried at 40°C for 0.05 h after each filling, and other conditions remain unchanged.

[0079] Comparative Example 6: It is basically the same as Example 1, except that in step S5 the firing temperature is adjusted to 1300℃, the firing time is still 0.5h, the firing pressure is still 0.080MPa, and the firing atmosphere is still composed of 99.9 vol% nitrogen and 0.1 vol% hydrogen. Other conditions remain unchanged.

[0080] Comparative Example 7: It is basically the same as Example 1, except that in step S5 the firing atmosphere is adjusted to 100.0 vol% nitrogen and no hydrogen is added, the firing temperature is still 1350°C, the firing time is still 0.5 h, the firing pressure is still 0.080 MPa, and other conditions remain unchanged.

[0081] Comparative Example 8: Basically the same as Example 1, except that in step S6 the nickel layer thickness is adjusted to 0.5 μm, the gold layer thickness remains 0.03 μm, and the sputtering pressure remains 1.0 × 10⁻⁶. -7 MPa, substrate temperature remains at 20℃, and other conditions remain unchanged.

[0082] Comparative Example 9: Essentially the same as Example 1, except that a ceramic shoulder forming area is not formed in step S2, the stepped through-wall hole is replaced with a straight through-wall hole, and the end face of the through-wall metal conductor is flush with the corresponding outer surface of the alumina ceramic sidewall. The radial width of the ceramic annular surface without exposed metal is 0.00 mm, with other conditions remaining unchanged. This comparative example is used to verify the synergistic effect of the ceramic shoulder and the retracted end face structure of the through-wall metal conductor.

[0083] Comparative Example 10: Essentially the same as Example 1, except that in step S2, the ceramic shoulder forming area and the ceramic annular surface without exposed metal are retained, and the end face of the through-wall metal conductor is flush with the corresponding outer surface of the alumina ceramic sidewall. The radial width of the ceramic annular surface without exposed metal remains 0.05 mm, and the shoulder width of the ceramic shoulder forming area remains 0.15 mm. Other conditions remain unchanged. During filling, the axial filling amount of the central slurry is increased, so that the slurry end face extends from the bottom of the expanded cavity to the corresponding outer surface of the alumina ceramic sidewall, while keeping the surrounding ceramic annular area uncovered by the slurry. This comparative example is used to verify the synergistic effect of the end face retraction and the ceramic annular surface without exposed metal.

[0084] Comparative Example 11: Essentially the same as Example 1, except that manganese powder was not added in step S3, and an equal mass of tungsten powder was used instead. The metallizing slurry was adjusted to a tungsten-molybdenum metallizing slurry with the following composition: 71.7 wt% tungsten powder, 2.0 wt% molybdenum powder, 1.0 wt% ethyl cellulose, and 25.3 wt% α-terpineol. The slurry was prepared using the same premixing, three-roll milling, and vacuum degassing steps as in Example 1, with other conditions remaining unchanged. This comparative example has the same non-volatile solids content and organic carrier content as Example 1, and is used to verify the effect of manganese on conductor densification and slurry rheological behavior.

[0085] Characterization and performance testing The exit geometry of the ceramic shoulder embedded conductive unit was measured to evaluate whether the retraction of the through-wall metal conductor end face, the radial width of the ceramic toroidal surface without exposed metal, and the shoulder width of the ceramic shoulder were formed as designed. The high-voltage ceramic sidewall semiconductor package was cut, embedded, and polished along the axial direction of the through-wall metal conductor. Images were acquired using an optical microscope or a cross-sectional microscope, and four exits were counted for each sample. When the number of exits for a single sample was less than four, all exits of that sample were measured, and similar exits from the same group of samples were merged to ensure that the number of exits in each group was not less than 12. The mean and standard deviation were calculated after calibration with an image scale. Data recording fields included the mean retraction, standard deviation of retraction, mean toroidal width, standard deviation of toroidal width, mean shoulder width, and standard deviation of shoulder width, in mm. The radial width of the ceramic toroidal surface without exposed metal was counted based on the minimum value obtained from the circumferential measurement of each exit; the inter-batch coefficients of variation for retraction and shoulder width were determined by referring to the calculation method for the inter-batch coefficient of variation for dimensional shrinkage.

[0086] The densification state of through-wall metallic conductors was tested to evaluate conductor filling integrity and closed-pore control level. Three-dimensional reconstructed images of the conductor filling channels were acquired using microfocus X-ray CT. The metal filling rate was calculated as the ratio of the solid metal volume to the conductor filling channel volume, and the closed-pore rate was calculated as the ratio of the pore volume not connected to the outer surface of the through-wall metallic conductor to the outer envelope volume of the through-wall metallic conductor. At least three samples were used in each group. Data fields included the average metal filling rate, standard deviation of the metal filling rate, average closed-pore rate, and standard deviation of the closed-pore rate, in vol%.

[0087] Inter-terminal withstand voltage and partial discharge initiation voltage were tested on the insulation path between the high-voltage and low-voltage through-wall metal conductors in high-voltage ceramic sidewall semiconductor packages. Samples were equilibrated for 24 hours at 25±2℃ and 45±10% relative humidity. A 50Hz AC effective voltage was applied at a rate of 0.5kVrms / s. After reaching the specified test voltage or the set upper limit, the voltage was held for 60 seconds, and the voltage state before breakdown, flashover, partial discharge, or other failures was recorded. Partial discharge measurement was recorded according to the applicable caliber for apparent charge measurement under AC voltage in IEC 60270:2025. The partial discharge initiation criterion was an apparent charge of not less than 5pC that persisted during the 60-second holding period. Test record fields included inter-terminal withstand voltage, partial discharge initiation voltage, applied voltage waveform, test frequency, voltage increase process, holding time, electrode connection method, apparent charge, background noise, and failure criteria.

[0088] The change in the amount of shrinkage at the end face of the through-wall metal conductor at the same outlet before and after thermal cycling was tested to evaluate the thermal stability of the interface between the ceramic shoulder and the metal conductor. The sample was cycled in an air environment ranging from -40℃ to 125℃, with holding at the low and high temperatures for 15 minutes each, and a transition time not exceeding 5 minutes. After 500 cycles, the sample was returned to room temperature. The shrinkage at the same outlet before and after thermal cycling was measured using non-destructive optical microscopy. The change in end face shrinkage was calculated by subtracting the shrinkage before thermal cycling from the shrinkage after thermal cycling. The absolute value of this change was used to evaluate the thermal cycling stability. Data fields include the average and standard deviation of the shrinkage change after thermal cycling, in mm.

[0089] The continuity coverage of the nickel-gold termination layer was tested to evaluate the termination integrity of the accessible end faces. Optical microscopy, scanning electron microscopy, or energy dispersive spectroscopy were used to observe the accessible end faces of the through-wall metal conductors. Overall images of the accessible end faces were acquired and thresholded. The percentage of the largest common coverage area with both nickel and gold layers that are interconnected was calculated relative to the total area of ​​the accessible end faces. Each group consisted of at least three samples, and at least four end faces were analyzed for each sample. Data fields included the average and standard deviation of the continuity coverage of the termination layer, in percentages (%).

[0090] Rheological and continuous filling state tests were performed on the tungsten-molybdenum-manganese metallization slurry. After vacuum degassing, the apparent viscosity of the slurry was measured using a rotational rheometer at 25±1℃. Unless otherwise specified in the rheological curve, the quality control apparent viscosity was maintained at a shear rate of 100 s⁻¹. -1 The apparent viscosity, temperature, and non-volatile solids content were measured under the specified conditions; rheological curves were recorded at different shear rates. Simultaneously, conductor-filled channels with a pore size of 0.08 mm were filled at a set pressure, and the proportion of continuously filled sections was observed after pre-drying. The proportion of continuously filled sections was calculated as the percentage of channels with no gaps and where the slurry filling section penetrated the entire conductor-filled channel out of the total number of observed channels. Data fields included the average apparent viscosity of the slurry, the standard deviation of the apparent viscosity of the slurry, and the average and standard deviation of the proportion of continuously filled sections, in Pa·s and %.

[0091] To verify the effectiveness of the high-voltage ceramic sidewall semiconductor package and its preparation method described in this invention, Example 1 was used as a representative sample, and the filling pressure, end-face retraction structure, partial discharge performance, pore characteristics, slurry rheological properties, and microstructure of the final product were systematically characterized. The test results show that this invention does not simply increase the filling amount of the through-wall metal conductor, but rather, while ensuring continuous conduction of the tungsten-molybdenum-manganese through-wall metal conductor, it reduces the risk of local electric field concentration and surface discharge caused by exposed metal ends through the synergistic design of the ceramic shoulder, end-face retraction, and the ceramic toroidal surface without exposed metal, thereby balancing conductivity reliability and high-voltage insulation stability.

[0092] First, such as Figure 1 As shown, with the slurry system and sintering regime of Example 1 remaining unchanged, the effect of filling pressure on the metal filling rate and partial discharge initiation voltage was investigated by only changing the filling pressure. The filling pressure was set to 0.02, 0.05, 0.15, 0.30, 0.45, 0.60, and 0.70 MPa. The results show that as the filling pressure increases, the sufficiency of the tungsten-molybdenum-manganese slurry entering the conductor filling channel is significantly improved, and the metal filling rate increases accordingly; when the filling pressure is about 0.45 MPa, the metal filling rate can reach about 97.8 vol%, and the partial discharge initiation voltage is about 6.4 kVrms. This result indicates that appropriately increasing the filling pressure can reduce the unfilled area and large-sized voids in the conductor filling channel, which is beneficial to the formation of a continuous and dense through-wall metal conductor. However, when the filling pressure continues to increase, although the metal filling rate may still remain at a high level, excessively high pressure can easily cause the slurry to be over-propelled towards the outlet end or the stability of the end morphology to decrease, which is not conducive to maintaining the accurate configuration of the ceramic shoulder and end face retraction structure. Therefore, Figure 1This demonstrates that the filling pressure used in this invention is not necessarily better the higher it is, but rather a balance is achieved between sufficient metal filling and stable end insulation structure. This balance is the technological basis for resolving the contradiction between "high filling conductivity" and "high withstand voltage insulation". 0.02 MPa and 0.70 MPa are comparative pressures used to examine boundary effects and are not considered as the preferred range for the filling pressure of this invention.

[0093] Based on the aforementioned process window, further... Figure 2 Verify the repeatability of the end-face retraction structure of the present invention. Figure 2 This is a quantitative diagram of the end-face retraction in cross-sectional images of Examples 1, 9, and 10. Statistical comparisons were made of the metal conductor end-face positions of different samples using multiple cross-sectional measurement points. The results show that the end-face retraction in Example 1 is mainly concentrated in the range of approximately 0.094-0.108 mm, close to and stably falling within the design target value of 0.10 mm, indicating that the tungsten-molybdenum-manganese through-wall metal conductor end-face can form a stable retraction relative to the outer surface of the alumina ceramic sidewall. The end-face retraction in Comparative Examples 9 and 10 is concentrated in the range close to 0 mm; however, Comparative Example 9 did not have a ceramic shoulder forming area, and although Comparative Example 10 retained the ceramic shoulder forming area and ceramic annular surface, its central metal end-face extended to the outer surface of the alumina ceramic sidewall, failing to form effective end-face retraction. Therefore, simply forming a through-wall metal conductor or merely retaining the outlet ceramic ring is insufficient to achieve the high-voltage end structure of this invention. Only through the joint control of the ceramic shoulder and the axial filling termination position of the slurry can the conductor end face reliably retract into the ceramic sidewall, forming a ceramic ring without exposed metal around the outlet. This structure separates the metal end from the outer surface boundary, reducing the local electric field concentration caused by sharp metal edges or flush metal end faces at the outlet, providing a structural prerequisite for subsequent improvement of partial discharge performance.

[0094] based on Figure 2 The proven end-face retraction and ceramic isolation structure, Figure 3 Further verification of its voltage withstand improvement effect from the perspective of electrical performance. Figure 3The apparent charge-applied voltage curves for Examples 1, 9, and 10 are shown to compare the discharge response of different outlet structures during the voltage boosting process. The results show that at an applied voltage of 3.0 kVrms, the apparent charge of Example 1 is approximately 5.1 pC, significantly lower than the approximately 16.0 pC of Comparative Example 9 and approximately 10.0 pC of Comparative Example 10. This indicates that, under the same voltage conditions, Example 1 significantly reduces end-discharge activity due to the retraction of the through-wall metal conductor end face relative to the ceramic sidewall surface, and the insulation provided by the ceramic shoulder and the ceramic ring face without exposed metal. Compared to the comparative examples, Example 1 does not passively improve the withstand voltage by increasing the overall external insulation size, but rather constructs a composite boundary of "ceramic ring face isolation - metal end face retraction - confined termination layer coverage" locally at the through-wall metal conductor outlet, suppressing discharge defects at the high-voltage outlet. Therefore, Figure 3 This directly proves that the structural design of this invention can translate end geometry optimization into actual partial discharge reduction.

[0095] Besides the end structure, the porosity within the through-wall metal conductor also affects conductivity continuity, mechanical stability, and local electric field distribution. Therefore, Figure 4 The equivalent diameter distribution of closed pores in Examples 1, 5, and 11 was compared. The results show that the closed pores in Example 1 are mainly concentrated in the smaller pore size range, with a peak region around 12 μm; while the pore size distributions in Comparative Examples 5 and 11 extend more significantly towards larger dimensions, indicating that larger closed defects are more easily formed inside. This result shows that Example 1 not only achieves a high metal filling rate but also controls the residual closed pores within a small size range. Smaller and more concentrated pores help reduce local non-uniformity of the conductive cross-section and the concentration of local thermal and mechanical stress caused by large pores. Therefore, the present invention ensures a high voltage-resistant structure at the ends without sacrificing the density and continuity of the through-wall metal conductor body.

[0096] Figure 5 This further illustrates the different effects of slurry rheological state and filling pressure on the aforementioned porosity control. Figure 5 The rheological curves of the tungsten-molybdenum-manganese metallization slurries of Example 1 and Comparative Example 5, and the tungsten-molybdenum metallization slurry of Comparative Example 11 are shown. Example 1 and Comparative Example 5 used the same formulation and preparation process for their tungsten-molybdenum-manganese metallization slurries; therefore, their rheological curves largely overlap within the test error range. Figure 4 The porosity differences observed in the samples mainly stem from variations in filling pressure, rather than differences in the slurry's rheological properties. Comparative Example 11, which replaced manganese powder with an equal mass of tungsten powder, exhibited a different rheological curve compared to Example 1, indicating that the composition of the metal powder also affects the slurry's viscosity response at different shear rates.

[0097] Example 1 at 10s -1 The apparent viscosity at the shear rate is approximately 80 Pa·s; this value is similar to that in Example 1 at 25±1℃ and a shear rate of 100 s. -1 The apparent viscosity measured under the condition of 20 Pa·s before filling corresponds to the quality control apparent viscosity. This rheological behavior indicates that during the filling process, the apparent viscosity of the slurry decreases under applied pressure and shear, allowing it to smoothly enter the fine conductor filling channel with a pore size of approximately 0.08 mm. Furthermore, under low shear conditions after filling, the initial apparent viscosity and solids content of the slurry are beneficial for maintaining the end morphology, preventing end collapse, overflow, or uncontrolled retraction. Therefore, the slurry system of Example 1 simultaneously satisfies the two mutually restrictive requirements of "entering fine channels under compressive shear" and "maintaining end morphology after filling," which is why it can achieve [the desired results]. Figure 1 The high metal filling rate shown Figure 2 The amount of retraction of the stable end face shown and Figure 4 This is an important reason for the distribution of small-sized pores shown.

[0098] at last, Figure 6 The structural validity of Example 1 was directly demonstrated by SEM morphology and SEM-EDS mapping of the final product. Figure 6 Figure a in the figure is a low-magnification SEM image of the final product of Example 1, showing that the overall structure of the alumina ceramic sidewall is continuous, the high-voltage end and the low-voltage end through-wall metal conductors are staggered, and the shortest surface distance corresponding to the outer outlet area is 1.5mm, indicating that Example 1 meets the high-voltage insulation spacing requirements in terms of overall structure. Figure 6 Figure b in the figure is a low-magnification SEM image of the final product of Comparative Example 9. Its overall ceramic sidewall morphology is comparable to that of Example 1, but no stepped ceramic shoulder and end face retraction structure are formed at the outer outlet, thus eliminating the main influence of the overall ceramic shape difference on the subsequent comparison results.

[0099] Further observation of the local structure at the export point, Figure 6Figure c shows that in Example 1, a conductor-filled channel with an aperture of 0.08 mm, a ceramic shoulder with a width of 0.15 mm, a tungsten-molybdenum-manganese through-wall metal conductor end face with a retraction of 0.10 mm, and a ceramic annular surface without exposed metal with a radial width of 0.05 mm are formed. Because the width of the ceramic shoulder is greater than the end face retraction, the central end of the through-wall metal conductor extends 0.05 mm from the bottom of the expanded cavity towards the outlet direction, but its end face is still 0.10 mm inside the outer surface of the alumina ceramic sidewall and does not cover the surrounding ceramic annular surface. The above dimensional relationships indicate that the width of the ceramic shoulder along the conductor axial direction is not less than the end face retraction, effectively shielding and supporting the retracted end face; simultaneously, the ceramic annular surface without exposed metal forms an insulating isolation zone around the outlet, preventing the metal conductor end face from being flush with the outer surface of the ceramic sidewall. In contrast, Figure 6 Figure d in the diagram shows that Comparative Example 9 is a straight-through wall hole structure, with its metal end face basically flush with the outer surface of the alumina ceramic side wall, and the ceramic shoulder and the ceramic annular surface without exposed metal are missing. Figure 6 Figure c in the middle and Figure 6 The comparison of the d-graphs shows that the stepped through-wall hole structure is the key structural condition for forming the end face retraction and ceramic isolation ring, and it is also the core difference between this invention and the conventional straight-through through-wall conductor structure.

[0100] At higher magnifications, Figure 6 Figure e shows that the interface between the alumina ceramic and the tungsten-molybdenum-manganese through-wall metal conductor in Example 1 is continuous. Although there are a few closed pores inside the conductor, the whole still forms a continuous conductive phase. The conductor filling rate is 92.0 vol%, and the closed pore rate is 5.0 vol%, indicating that the through-wall metal conductor can maintain effective communication in the small channels after firing. Figure 6 Figure f in Comparative Example 9 shows that the metal phase near the flush end face is partially in contact with the outer surface of the ceramic. The metal end face is directly at the outer outlet boundary, making it easier to form a local electric field concentration and discharge initiation point. This comparison further illustrates that the present invention does not sacrifice insulation performance by reducing the degree of metallization, but rather achieves a balance between conductivity and insulation performance by moving the metal end backward from the outer surface boundary while maintaining conductor continuity.

[0101] Figure 6 g-graph and Figure 6 The SEM-EDS Mapping results of the h-plot further validate the above structural differences from the perspective of element distribution. Figure 6In Figure g, Al and O signals mainly correspond to the alumina ceramic sidewalls and the ceramic annulus around the outlet without exposed metal; W, Mo, and Mn signals correspond to the tungsten-molybdenum-manganese through-wall metal conductor; and Ni and Au signals correspond to the nickel-gold termination layer on the accessible end face. Furthermore, the nickel and gold layers do not cover the ceramic annulus, indicating that Example 1 achieves spatial separation between the ceramic insulation region, the metal conductor region, and the termination layer at the microscale. In contrast, Figure 6 In Figure h, the W, Mo, Mn, Ni, and Au signals in Comparative Example 9 correspond to the through-hole and flush metal end-face regions, lacking the approximately 0.05mm ceramic annular isolation band dominated by Al and O. This result demonstrates that the ceramic shoulder and end-face retraction structure described in this invention not only exists in geometry but also effectively constrains the spatial boundaries of the metal elements and termination layer at the outer exit, preventing the metal termination layer from crossing or covering the insulation isolation area.

[0102] In conclusion, Figures 1 to 6 The effectiveness of the present invention was demonstrated sequentially from aspects such as process parameters, end geometry, electrical response, internal porosity, slurry rheology, and final micro-elemental partitioning. Example 1 achieves full filling of the fine conductor filling channel through appropriate filling pressure and shear-thinned tungsten-molybdenum-manganese metallization slurry. The ceramic shoulder causes a retraction of approximately 0.10 mm at the end face of the through-wall metal conductor, and a ceramic annular surface with a radial width of approximately 0.05 mm around the outlet without exposed metal is formed, while simultaneously ensuring conductor filling rate and interface continuity. Therefore, the present invention effectively solves the contradiction in existing ceramic sidewall through-wall conductor structures between "the need for sufficient filling of the metal conductor to ensure reliable conduction" and "exposed metal end faces easily lead to partial discharge and reduced withstand voltage," achieving a synergistic improvement in high filling rate, high conduction, and high end withstand voltage insulation of the through-wall conductor.

[0103] Table 1 Performance of Examples and Comparative Examples ; Note: For samples that do not fail or partially discharge within the test upper limit, the voltage result is recorded as "not lower than the test upper limit, and no corresponding failure has occurred"; for samples that fail or show signs of partial discharge initiation within the test range, the voltage result is recorded as the average value ± standard deviation. The continuous coverage of the termination layer is uniformly expressed as the average value ± standard deviation, with an upper limit not exceeding 100.0%. The average shrinkage change after thermal cycling is a signed change calculated as "shrinkage after thermal cycling minus shrinkage before thermal cycling"; its absolute value is used to evaluate thermal cycling stability.

[0104] As can be seen from the test results of the examples and comparative examples in Table 1, Example 1 maintained a metal filling rate of 92.0 vol%, a continuous coverage of the termination layer of 95.0%, and a terminal withstand voltage of 5.0 kVrms under low-value structure and mild process conditions. Examples 2 and 4, under the combination of larger sidewall dimensions, longer surface distance, higher filling pressure, higher firing intensity, and thicker termination layer, did not experience corresponding failures or partial discharges within the set test upper limit. After changing the ceramic additives in Comparative Examples 1 and 2, the metal filling rate, withstand voltage, and thermal cycling stability decreased simultaneously; after changing the shrinkage relationship of the outlet ceramic annular surface or end face in Comparative Examples 4, 9, and 10, the partial discharge initiation voltage decreased; Comparative Examples 5, 6, 7, and 11 reflect the effects of filling pressure, firing temperature, reducing atmosphere, and metallic manganese on conductor densification.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high-voltage ceramic sidewall semiconductor package, characterized in that, include: Alumina ceramic base; An alumina ceramic sidewall is disposed on the alumina ceramic base and together with the alumina ceramic base forms the component receiving cavity; as well as A tungsten-molybdenum-manganese through-wall metallic conductor penetrating the alumina ceramic sidewall; Wherein, the alumina ceramic sidewall forms a ceramic shoulder at at least one outlet of the through-wall metal conductor, the ceramic shoulder causing the end face of the through-wall metal conductor to retract by 0.10-0.60 mm relative to the corresponding surface of the alumina ceramic sidewall, the corresponding surface being the inner or outer surface of the alumina ceramic sidewall adjacent to the outlet; The ceramic shoulder forms a non-metallic ceramic annular surface around the outlet of the through-wall metal conductor. The non-metallic ceramic annular surface is made of alumina ceramic and is not covered by the through-wall metal conductor. The radial width of the non-metallic ceramic annular surface is 0.05-0.50 mm. The shoulder width of the ceramic shoulder along the axial direction of the through-wall metal conductor is 0.15-0.80 mm, and the shoulder width at the same outlet is not less than the corresponding end face retraction.

2. The high-voltage ceramic sidewall semiconductor package according to claim 1, characterized in that, The alumina ceramic sidewall comprises alumina, silicon dioxide, and magnesium oxide. The content of each component is calculated by oxide equivalent. Specifically, based on a total inorganic solid mass of 100 wt% for the alumina ceramic sidewall, the content of silicon dioxide is 0.1-5.0 wt%, the content of magnesium oxide is 0.1-3.0 wt%, and the balance is alumina. The sum of the mass percentages of alumina, silicon dioxide, and magnesium oxide is 100 wt%. The tungsten-molybdenum-manganese through-wall metal conductor comprises metallic tungsten, metallic molybdenum, and metallic manganese. Based on a total metal mass of 100 wt%, the content of metallic molybdenum is 0.5-15.0 wt%, the content of metallic manganese is 0.1-10.0 wt%, and the content of metallic tungsten is 75.0-95.0 wt%. The sum of the mass percentages of metallic tungsten, metallic molybdenum, and metallic manganese is 100 wt%.

3. The high-voltage ceramic sidewall semiconductor package according to claim 1, characterized in that, The through-wall metal conductor and the ceramic shoulder together constitute a ceramic shoulder embedded conductive unit, which is prepared by the following steps: A1. Alumina ceramic sidewall preform is provided, the alumina ceramic sidewall preform comprising alumina, silicon dioxide and magnesium oxide; A2. A stepped through-wall hole is formed on the alumina ceramic sidewall blank, the stepped through-wall hole including a conductor filling channel and a ceramic shoulder forming area located at at least one outlet of the conductor filling channel; A3. Fill the conductor filling channel with tungsten-molybdenum-manganese metallization slurry, control the axial filling termination position of the tungsten-molybdenum-manganese metallization slurry according to the target end face retraction amount, and control the tungsten-molybdenum-manganese metallization slurry to not cover the ceramic annular area surrounding the conductor filling channel in the ceramic shoulder forming area, so as to obtain the filled alumina ceramic sidewall blank. A4. Dry the filled alumina ceramic sidewall blank; A5. Firing in a firing atmosphere composed of nitrogen and hydrogen to form a through-wall metal conductor; A6. After firing, the ceramic shoulder embedded conductive unit is obtained by cleaning and drying. The ceramic shoulder embedded conductive unit satisfies the following conditions: the through-wall metal conductor is continuously continuous, the end face of the through-wall metal conductor is retracted by 0.10-0.60mm relative to the corresponding surface of the alumina ceramic sidewall, and the radial width of the ceramic annular surface without exposed metal is 0.05-0.50mm. The ceramic shoulder embedded conductive unit also satisfies the following requirements: the metal filling rate in the conductor filling channel is 92.0-99.5 vol, and the closed porosity in the through-wall metal conductor is 0.1-5.0 vol.

4. The high-voltage ceramic sidewall semiconductor package according to claim 3, characterized in that, In step A5, the hydrogen content in the firing atmosphere is 0.1-5.0 vol% on a dry basis, the sum of the volume fractions of nitrogen and hydrogen is 100.0 vol%, the firing temperature is 1350-1550℃, the firing time is 0.5-3.0 h, and the firing pressure is 0.080-0.110 MPa, where the firing pressure is the total absolute pressure of the firing atmosphere. In step A6, the drying temperature after cleaning is 60-100℃, and the drying time is 0.5-3.0h.

5. The high-voltage ceramic sidewall semiconductor package according to claim 3, characterized in that, The tungsten-molybdenum-manganese metallization slurry is prepared through the following steps: B1. Weigh out tungsten powder, molybdenum powder, manganese powder, ethyl cellulose, and α-terpineol; B2. Premix the tungsten powder, the molybdenum powder, and the manganese powder in a nitrogen atmosphere to obtain a premixed metal powder; B3. Add the ethyl cellulose and α-terpineol to the premixed metal powder and disperse them; B4. Vacuum degassing to obtain the tungsten-molybdenum-manganese metallization slurry; The tungsten-molybdenum-manganese metallization paste satisfies the following condition: the paste can continuously fill the conductor filling channel; The tungsten-molybdenum-manganese metallization slurry also meets the following requirements: based on a total mass of 100wt% of the tungsten-molybdenum-manganese metallization slurry, the total content of tungsten powder, molybdenum powder, manganese powder, and ethyl cellulose, i.e., the non-volatile solids content, is 74.0-92.0wt%, and is suitable for use at 25±1℃ and a shear rate of 100s. -1 The apparent viscosity measured under these conditions was 20-200 Pa·s.

6. The high-voltage ceramic sidewall semiconductor package according to claim 3, characterized in that, The alumina ceramic sidewall preform is prepared by the following steps: C1. Weigh alumina powder, silica powder and magnesium oxide powder to obtain inorganic powder; C2. Add polyvinyl butyral, polyethylene glycol 400 and ethanol to the inorganic powder; C3. Mix and shape into a ceramic sidewall green body; C4. Dry the ceramic sidewall green body; C5. Degrease and sinter the dried ceramic sidewall green body to obtain the alumina ceramic sidewall green body; The alumina ceramic sidewall preform meets the following requirements: open porosity of 0.1-5.0 vol% and batch-to-batch coefficient of variation for dimensional shrinkage of 0.1-3.0%.

7. The high-voltage ceramic sidewall semiconductor package according to claim 1, characterized in that, A nickel-gold termination layer is disposed on the accessible end face of the through-wall metal conductor. The nickel-gold termination layer does not cover the ceramic annular surface without exposed metal. The nickel-gold termination layer is prepared by the following steps: D1. Clean and dry the accessible end face of the through-wall metal conductor; D2. Using a masking film that exposes only the accessible end face, and using a metallic nickel target as the nickel source, the accessible end face is locally sputtered in an argon atmosphere to form a nickel layer; D3. Using the aforementioned masking film and a gold target as the gold source, a gold layer is formed by local sputtering on the nickel layer in an argon atmosphere; The nickel-gold termination layer satisfies the following conditions: the nickel layer covers the accessible end face of the through-wall metal conductor, the gold layer covers the nickel layer, and the nickel layer and the gold layer form a common continuous coverage area on the accessible end face; The nickel-gold termination layer also satisfies the following requirements: the nickel layer thickness is 1.0-8.0 μm, the gold layer thickness is 0.03-1.00 μm, and the continuous coverage of the termination layer on the accessible end face is 95.0-100.0%.

8. The high-voltage ceramic sidewall semiconductor package according to claim 1, characterized in that, The ceramic shoulder is simultaneously provided at the inner and outer outlets of the through-wall metal conductor, and the inner and outer end faces of the through-wall metal conductor are both retracted by 0.10-0.60 mm relative to the corresponding alumina ceramic sidewall surface. The through-wall metal conductor includes a high-voltage end through-wall metal conductor and a low-voltage end through-wall metal conductor. The high-voltage end through-wall metal conductor and the low-voltage end through-wall metal conductor are staggered in the height direction or circumferential direction of the alumina ceramic sidewall, and the shortest surface distance between them is 1.5-12.0 mm. The thickness of the alumina ceramic sidewall is 0.30-1.50 mm, and at the same through-wall metal conductor, the thickness of the alumina ceramic sidewall is greater than the sum of the shoulder width of the inner ceramic shoulder and the shoulder width of the outer ceramic shoulder. The height of the alumina ceramic sidewall is 0.60-4.00 mm. The alumina ceramic sidewall has a conductor filling channel for the through-wall metal conductor to pass through, and the aperture of the conductor filling channel is 0.08-0.50 mm.

9. A method for preparing a high-voltage-resistant ceramic sidewall semiconductor package according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Provides an alumina ceramic base and an alumina ceramic sidewall blank; S2. A stepped through-wall hole is formed on the alumina ceramic sidewall blank, the stepped through-wall hole including a conductor filling channel and a ceramic shoulder forming area located at at least one outlet of the conductor filling channel; S3. The conductor filling channel is filled with tungsten-molybdenum-manganese metallization slurry. The axial filling termination position of the tungsten-molybdenum-manganese metallization slurry is controlled according to the target end face retraction amount. The tungsten-molybdenum-manganese metallization slurry is controlled not to cover the ceramic annular area surrounding the conductor filling channel in the ceramic shoulder forming area, so as to obtain the filled alumina ceramic sidewall blank. S4. Dry the filled alumina ceramic sidewall blank; S5. Firing in a firing atmosphere composed of nitrogen and hydrogen to form a through-wall metal conductor that is 0.10-0.60 mm retracted relative to the surface of the alumina ceramic sidewall; S6. After forming a nickel-gold termination layer on the accessible end face of the through-wall metal conductor, the sintered alumina ceramic sidewall is positioned and fixed on the alumina ceramic base, so that the alumina ceramic sidewall and the alumina ceramic base together define the component receiving cavity, thereby obtaining the high-voltage ceramic sidewall semiconductor package.

10. The method according to claim 9, characterized in that, In step S2, the stepped through-wall hole is formed by laser processing, mechanical grinding or a combination thereof, the diameter of the conductor filling channel is 0.08-0.50mm, the shoulder width of the ceramic shoulder forming area along the axial direction of the through-wall metal conductor is 0.15-0.80mm, and the shoulder width of the ceramic shoulder forming area is not less than the corresponding target end face retraction amount. In step S3, the tungsten-molybdenum-manganese metallization slurry is filled into the conductor filling channel under a gauge pressure of 0.05-0.60 MPa relative to the ambient pressure. The filling is performed 1-5 times, and after each filling, the material is pre-dried at 40-90°C for 0.05-0.50 h.

Citation Information

Patent Citations

  • Alumina ceramic, and ceramic wiring substrate and ceramic package using same

    CN103732558A

  • Alumina multilayer ceramic tungsten metallide slurry and preparation method thereof

    CN105060940A